Changes of Human Gut Microbiome Correlated with Metabolomics After Cranberry Juice Consumption in a Double-Blinded, Placebo Controlled, Crossover Study. (29th May 2020) - Zhao, Shaomin; Wang, Gary; Liu, Haiyan; Khoo, Christina; Gu, Liwei
Abstract: Objectives: 1) To investigate the changes of gut microbiome after 3 days and 21 days of cranberry juice consumption; 2) to correlate changes of microbiome with metabolome. Methods: A double blinded, placebo-controlled, cross-over intervention study were conducted in 17 healthy young women aged 18–29 with normal BMI. Fecal, urine, and plasma samples were collected at baseline, after 3 days, and after 21 days consumption of double strength cranberry juice or a placebo juice. DNA was extracted from fecal samples and 16s rRNA was sequenced. Discriminant metabolites in urine and plasma was analyzed by UHPLC-Q-Orbitrap-HRMS and 0 identified using OPLS-DA models. Results: 21-days but not 3 days of cranberry juice consumption significantly increased alpha diversity of colon microbiome compared to baseline. Significant increase in the abundance of Firmicutes, Ruminococcaceae, Faecalibacterium, and F/B (Firmicutes to Bacteroidetes) ratios were found after 21-days of cranberry juice intake. This was accompanied by decreases in Bacteroidetes, Proteobacteria, Clostridia, Enterobacteriaceae, Veillonellaceae, Bacteroides, Parabacteroides, and Enterobacter. Gut microbial composition before and after 21-days of cranberry juice consumption was significantly per Bray-Curtis dissimilarity analysis. However, cranberry consumption did not alter fecal content of short chain fatty acids, ammonia, or mucin. Spearman's correlation analysis showed significant positive or negative correlations between selected strains of bacteria and discriminant metabolites. 4-O-methylgallic acid was a discriminant metabolite in urine after 21-days of cranberry juice consumption. Its content positively correlated with Parabacteroides but negatively correlated with Faecalibacterium ( P < 0.05). 3-(Hydroxyphenyl) propionic acid was a discriminant metabolite in plasma after cranberry juice consumption. Its content negatively correlated with Enterobacteriaceae ( P < 0.05). Conclusions: 21-days but not 3 days of cranberry juice consumption significantly altered colon microbiome. Correlation between gut bacteria and plasma, urine metabolites suggested interaction between gut microbiome and serum and urine metabolome. Funding Sources: This research is funded in part by Ocean Spray Cranberries, inc.